ENT problems of the general population: a health centre experience - Sahoo, Soumick Ranjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
At present a lot of focus is being made in making healthcare accessible to all people. Many patients prefer to visit the health centre close to their homes. Among the clinical complaints for which a patient visits a health centre, ENT complaints constitute an important category. An attempt was made to get an idea of the otorhinolaryngology complaints/disorders for which patients visited the health centre attached to the main hospital and located near a residential area by spending few hours a day few days a week at the health centre. The most common diagnosis as per the study was upper respiratory tract infection. It is felt that health centre can be utilized to carry out otorhinolaryngology research, education and training of primary care providers on ENT pathology and for providing healthcare services to the people. This will bring uniformity in the level of ENT care and the services will reach those people who are unable to visit the main hospital especially senior citizens. This manuscript may also help the policymakers to implement the health centre model in different Primary Health Centre /Sub Centre/Urban Health Centre/Community Health Centre of India and promoting the concept of Community otorhinolaryngology.